Pseudovascular adenoid squamous cell carcinoma of the tongue: a case report and literature review - Han, Xiaodong (Int J Clin Exp Pathol, 2020)
Pseudovascular adenoid squamous cell carcinoma (PASCC) is an uncommon histologic variant of squamous cell carcinoma, characterized by acantholysis in the cancer nests resulting in a pseudovascular appearance, and a subtype of acantholytic squamous cell carcinoma. It is relatively common in sun-exposed skin, but is extremely rare in oral cavity. A 56-year-old woman was referred to our department presented with a fast-growing mass in the front of the tongue for more than two months. Physical examination revealed a exophytic lesion with a pedicle in the anterior tongue. An incisional biopsy was performed. On microscopic examination, the tumor was composed of vessel-like anastomosing channels and dilated vessel-like spaces, similar to hemangioma, and the anastomosing channels contained free tumor cells. The nests of tumor cells with significant acantholysis were observed in some regions. Immunohistochemical examination revealed cells positive for pan-CK, CK5/6, p63, and negative for CD31 and CD34. The pathological diagnosis was confirmed as pseudovascular adenoid squamous cell carcinoma. The extended resection of the tumor and neck dissection was performed. There was no tumor recurrence or distant metastasis after 15 months of follow-up.